Combination of In Silico Analysis and In Vitro Assay to Investigate Drug Response to Human Epidermal Growth Factor Receptor 2 Mutations in Lung Cancer. Issue 1 (21st October 2015) - Yu, Xiyan; Wang, Tong; Lou, Ying; Li, Yanwen
Abstract: The epidermal growth factor receptor 2 (HER2) has been established as an important target of HER2‐positive lung cancer, but somatic mutations in HER2 kinase domain are frequently observed that may cause drug resistance and sensitivity for tyrosine kinase inhibitors (TKIs). In this study, the response profile of 14 small‐molecule TKIs upon 11 clinical HER2 mutations was investigated systematically using a synthetic strategy that integrated in silico analysis and in vitro assay to explore the structural basis, energetic property and biological implication underlying the intermolecular interactions of TKIs with wild‐type and variant HER2. It is found that most clinical mutations are far away from HER2 active site and thus can only address modest or moderate effect on inhibitor binding. However, few single‐point substations such as D769H and D769Y as well as the gatekeeper mutation T798 M were predicted to cause strong resistance for an array of TKIs by reshaping the geometric feature and physiochemical property of the active site. Furthermore, inhibitor response to the most common insertion mutation in HER2 exion 20 (HER2 YVMA ) was examined in detail; the response can be grouped into three classes: sensitization, resistance and insusceptibility. The Bcr‐Abl inhibitor bosutinib and EGFR inhibitor gefitinib were selected as the representatives of, respectively, sensitization and insusceptibility to perform kinase assay against the GST‐tagged, recombinant kinase domains of wild‐type HER2 WT and HER2 YVMA variant. As expected, the biological activity of bosutinib was improved by ∼160‐fold due to the insertion, while gefitinib exhibited low inhibitory potency on both HER2 WT and HER2 YVMA (IC50 >100 μM). Structural analysis revealed an intensive network of hydrogen bonds and hydrophobic interactions in HER2 YVMA bosutinib complex, whereas only few nonspecific van der Waals contacts were observed at the complex interface of HER2 YVMA with gefitinib. Abstract :